MANAJEMEN LABA DAN PENERAPAN UU No.36/2008 TENTANG PERUBAHAN PENGHITUNGAN PAJAK PENGHASILAN - Eko Arief Sudaryono; Doddy Setiawan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2015)
This research aims at examining earnings management around Law Nu.36/2008 regarding tax tarif. Indonesian government change tax tarif from progressive tarif to single tarif. Indonesian government also provide incentives for listed companies. There is 5% reduction in tax tarif for listed companies. Sample of this research consists of non-financial firms in Indonesian Stock Exchange during 2006–2010 observations. The result of this research shows that there is no significant different between earnings management before and after the application single tarif for tax. This result is consistent using compare means test and regression analysis. Further analysis shows that ROA and leverage have positive effect on earnings management. Thus, leveraged firms are engaged in earnings management actively. This result also finds similar effect of ROA on earnings management. Firms with high earnings are more aggressive to manage earnings. On the other hand, this research does not find significant effect of firm size on earnings management.